Classroom Activities to Teach Writing for Elementary Students: EFL Teachers’ Preferences and Reasons - Khusna, Endah Noor Amalia; Puspitasari, Evi (Universitas Muhammadiyah Yogyakarta, 2020)
In order to be fluent in English, writing is one of skills that should be mastered by students. To assist and facilitate students in enhancing their writing skills, teachers need to create interesting and captivating activities. Unlike adolescences and adults, teaching writing for primary students is more challenging because at the elementary school stage students' writing ability is still at the elementary level. Additionally, teachers need to have creative for classroom activities. This qualitative study aims to explore classroom activities used by EFL primary school teachers in teaching writing and discuss what aspects of the skill that they focused on in teaching writing. For data collection techniques, the researcher interviewed five EFL teachers from five different elementary schools. The participants in this research had teaching elementary school students more than 5 years. The interviews were conducted through WhatsApp chat because the situation does not support conducting direct interviews during a pandemic. After the data obtained, transcribed, member checked, interpreted, and coded, the findings showed activities implemented to teach writing to elementary students preferred by the participants. The data in this study indicate that the activities used by the teacher to teach writing are simple activities like describing picture, free writing, and completing story. In addition, this study also reveals the purpose of teachers in teaching writing to elementary school students like a teacher wants to foster students’ love for writing. The results in this study indicate that in teaching writing to elementary school students, teachers need appropriate activities, so that the learning objectives can be achieved through these activities.